Pelatihan Wirausaha Digital kepada Jemaat Gereja Pentakosta Indonesia Sidang Paya Kapar Tebingtinggi - Gloria Sirait; Irving Josafat Alexander; Susanti; Timotius Agung Soripada; Sunggu Sirait (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Basically, entrepreneurship training is training that provides entrepreneurial skills, fosters motivation and interest in entrepreneurship so that participants gain increased skills, knowledge, experience and ability to become entrepreneurs. In this digital era, entrepreneurs are required to be more adaptive and innovative. They need to utilize digital technology to improve operational efficiency, expand market reach, and create added value for customers. This service activity uses a training approach as the main instrument. The pre-activity stage begins with identifying the needs and potential of the church congregation, including mapping the participants' abilities and shortcomings. Furthermore, the preparation of training materials tailored to the participants' needs was carried out carefully, taking into account various aspects such as digital knowledge, understanding of business and entrepreneurial potential. From the service activities that have been carried out, it can be concluded that this activity has considerable benefits for improving participants' digital entrepreneurship skills and knowledge. Participants also showed high enthusiasm as evidenced by the many questions from the participants. It is hoped that this entrepreneurship training and mentoring will be useful and can increase the knowledge, abilities and skills of digital entrepreneurship for the participants.